The future of private international law in the americas: reflections on the occasion of the celebration of the 50th anniversary of the First Inter-American Specialized Conference On Private International Law - Negro Alvarado, Dante (2024)
Private international law in the Americas was successfully and consistently developed in recent decades through the Inter-American Specialized Conferences, an organ of the Organization of American States, and whose starting point was CIDIP-I, held 50 years ago, in 1975. The last Conference was convened 15 years ago, which might show a certain paralysis of the codification process. Given the important contribution that the region has made to the development of universal private international law and the great impact that the results of the Specialized Conferences had on transnational private relations, it is more than necessary to explore what are the tools and mechanisms that the inter-American system itself offers us today to resume the codification and progressive development of this branch of law, including, if applicable, the use of soft law rules. To take a look at the work of the Specialized Conferences, we have drawn on the writings and contributions of leading specialists in private international law in the Americas. To construct specific proposals for the future, we have used official documents of the Organization of American States which provide us with an approach to the political decisions that, although still incipient, allow us to glimpse the future of this branch of law in our region. With this, we hope to be able to provide concrete alternatives that can be evaluated and supported decisively by both government authorities and experts and specialists on the continent.